2010
DOI: 10.4269/ajtmh.2010.09-0245
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Dissemination of Newly Introduced Plasmodium vivax Genotypes in South Korea

Abstract: Abstract. Reemerged Plasmodium vivax malaria in South Korea has not yet been eradicated despite continuous governmental efforts. It has rather become an endemic disease. Our study aimed to determine the genetic diversity in P. vivax merozoite surface protein-1 (PvMSP-1) and circumsporozoite protein (PvCSP) genes over an extended period after its reemergence to its current status. Sequence analysis of PvMSP-1 gene sequences from the 632 P. vivax isolates during 1996-2007 indicates that most isolates recently ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 30 publications
7
49
1
Order By: Relevance
“…Until recently, the number of type sequences in VB6 (similar to the ICB5-6 region) seemed to be restricted to four. These four type sequences (type 1 and variant, and types 2 and 4) of Pvmsp-1 VB6 from the Korean isolates from this study were similar to the previously reported S-a, S-b, B-1, and B-2, respectively (Choi et al 2010). Although this VB sequence was found to be a major recombinant type before 2000, Sal-1-and Belem-like types appeared in the Korean isolates only after 2000 (Choi et al 2010).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Until recently, the number of type sequences in VB6 (similar to the ICB5-6 region) seemed to be restricted to four. These four type sequences (type 1 and variant, and types 2 and 4) of Pvmsp-1 VB6 from the Korean isolates from this study were similar to the previously reported S-a, S-b, B-1, and B-2, respectively (Choi et al 2010). Although this VB sequence was found to be a major recombinant type before 2000, Sal-1-and Belem-like types appeared in the Korean isolates only after 2000 (Choi et al 2010).…”
Section: Discussionsupporting
confidence: 83%
“…These four type sequences (type 1 and variant, and types 2 and 4) of Pvmsp-1 VB6 from the Korean isolates from this study were similar to the previously reported S-a, S-b, B-1, and B-2, respectively (Choi et al 2010). Although this VB sequence was found to be a major recombinant type before 2000, Sal-1-and Belem-like types appeared in the Korean isolates only after 2000 (Choi et al 2010). In this study, a Sal-1-like type in VB2b of Pvmsp-1 was a major allelic type before 2000 and a Belem-like type of VB2a was found in the 2007 to 2009 samples.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…vivax in different populations. [16][17][18][19][20][21][22][23] However, investigations on polymorphism of the whole pvmsp1 have until now been limited. 13 In this study, we report polymorphism of pvmsp1 from isolates in Sanliurfa, southeastern Turkey, where malaria has long been one of the most common infectious diseases and P. vivax has continuously been identified as the only Plasmodium species.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the nature of the reemerging P. vivax in South Korea, several studies have attempted to analyze the genetic characteristics of P. vivax Korean isolates (Lim et al, 2000;Choi et al, 2010;Kang et al, 2012;Ju et al, 2013;Kang et al, 2014;Kang et al, 2015). However, these studies focused on simple polymorphism analysis of a single independent gene over a short time period or used limited numbers of isolates for the analyses.…”
Section: Introductionmentioning
confidence: 98%